Prevalência de ansiedade em estudantes do curso de Medicina da Universidade Federal da Paraíba - Silva, Marcos Andre Azevedo da (2024)
The prevalence of anxiety in the general population is increasing. Among the environments considered stressful, universities stand out. Thus, discussions about mental health among university students, with an emphasis on medical students, have gained prominence in recent years. From this perspective, the present study aimed to conduct a systematic literature review on the prevalence of anxiety among health students and to identify the prevalence and associated factors of anxiety among medical students at UFPB. The systematic literature review produced over the last 10 years was guided by the question: “What is the prevalence of anxiety in undergraduate health students?” Evidence indicated a significant prevalence of anxiety among health students, with a concentration of studies on medical students, making it difficult to compare between courses. The cross-sectional study was conducted with medical students from UFPB, aiming to assess the prevalence of anxiety using the State-Trait Anxiety Inventory. Data analysis was performed using Pearson's Chi-square test to verify the significance of variables and Robust Poisson Regression to determine the prevalence ratio between significant variables and anxiety. The results indicated a prevalence of anxiety of 62.5% among students. The associated factors that had a statistically significant prevalence ratio with anxiety were: being female (PR: 1.44; CI: 1.03 – 5.38), having lower income (PR: 1.18; CI: 1.00 – 1.39), receiving psychological counseling (PR: 1.23; CI: 1.053 – 1.437), using psychotropic drugs (PR: 1.36; CI: 1.14 – 1.63), and engaging in regular physical activity (PR: 0.69; CI: 0.59 – 0.79). The high prevalence rate of anxiety among university students highlights the need to create institutional measures aimed at identifying and controlling the mental health issues of students.